WIDE Research Center as an Incubator for Graduate Student Experience. (April 2017) - Turner, Heather Noel; Nguyen, Minh-Tam; Keller, Beth; Sackey, Donnie Johnson; Ridolfo, Jim; Pigg, Stacey; Lauren, Benjamin; Potts, Liza; Hart-Davidson, Bill; Grabill, Jeff
This article describes graduate mentorship experiences at the Writing, Information, and Digital Experience (WIDE) research center at Michigan State University and offers a stance on graduate student mentorship. It describes WIDE's mentorship model as feminist and inclusive and as a means to invite researchers with different backgrounds to engage in knowledge-making activities and collaborate on projects. Additionally, the article explains how WIDE enables growth for its researchers, teachers, and leaders. To illustrate these ideas, the authors provide multiple perspectives across faculty mentors, former graduate students, and current graduate students in order to discuss how WIDE researchers practice mentorship and how this mentorship prepares students for future work as scholars and researchers. Finally, the article suggests ways other research centers can adapt WIDE's approach to their own institutional context.